Three PAs talk about success in Mississippi. Issue 5 (May 2017) - Harris, Tristen A.; Butler, Kenneth R.
Abstract : ABSTRACT: This article gives the first-hand perspectives of three physician assistants (PAs) involved in the profession's years of struggle to gain practice authority in Mississippi. Through a series of questions and answers, each PA describes his or her part in the historical events that made Mississippi the final US state to regulate PAs.